2014
DOI: 10.1080/07924259.2013.875951
|View full text |Cite
|
Sign up to set email alerts
|

Experimental influence of pH on the early life-stages of sea urchins II: increasing parental exposure times gives rise to different responses

Abstract: 18Many studies into the responses of early life-stages to ocean acidification utilise offspring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…; Suckling et al. ), as previously discussed. Within‐generation acclimation can refer to both nonpermanent responses (i.e.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…; Suckling et al. ), as previously discussed. Within‐generation acclimation can refer to both nonpermanent responses (i.e.…”
Section: Discussionmentioning
confidence: 62%
“…; Suckling et al. ). Furthermore, the majority of trans‐generational experiments have been restricted across one, or maximum two, generations leaving it unclear whether or not adaptive TGP can extend into future generations allowing time for evolutionary adaptation to catch up (Chevin et al.…”
Section: Introductionmentioning
confidence: 98%
“…Our results suggest that unless exposure balances out differences in sensitivity, warming could disproportionately impact younger life stages, making this an even more pronounced bottleneck in population dynamics (O Donnell et al 2009, Findlay et al , Russell et al ). Future studies would ideally investigate the physiological and ecological mechanisms of persistence across life stages, including potential for acclimation, adaptation and migration (Sorte et al , , Suckling et al , , Parker et al , Samani and Bell ), to predict the impacts of climate change on marine invertebrate species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published since the AR5 have expanded on the longer-term responses to ocean acidification and have found that transgenerational and evolutionary responses can partly mitigate adverse effects, for example, in phytoplankton (75), planktonic crustaceans (76), sea urchins (77), and fish (78).…”
Section: Ocean Acidificationmentioning
confidence: 99%